ANALISA DAMPAK PERUBAHAN IKLIM TERHADAP KELONGSORAN DENGAN MENGESTIMASI PENURUNAN NILAI KOHESIVITAS TANAH - Anggraini, Nita; San, Indra Chusaini; Hastuti, Yulia (CANTILEVER, 2016)
Landslides is estimated to increase in the future as the impact of climate change, especially in changing of precipitation patterns, both of intensity and duration. Landslides are influenced by the rainfall duration that has a long duration and in infiltration capacity. The effect of infiltration of ground water causes volumetric water content increases and groundwater table recharge, which converts unsaturated soils become saturated soil. The longer infiltration causes soil cohesion decrease which is an indication of soil strenght decrease. It can be described by the relationship between the IDF(Intensity-Duration Frequency) curve, Hydraulic Conductivity curve, Soil Water Characteristic curve of slope stability analysis. This research will model the slope stability conditions at baseline (condition 30 years back) and when the projection (condition 30 years future) using the program SLOPE/w.